A RISK ASSESSMENT OF RUNOFF OF SOME EXTERNAL FUNDS OF A BANK - Boris M. Fedorov (Статистика и экономика)
The article describes the main steps for creating a model of risk assessment of runoff of external funds: the formation of training set, the selection of factor variables, and the estimation of parameters model. The result of the creation the model is given as an assessment of model accuracy.